2019
DOI: 10.1038/s41467-019-08463-z
|View full text |Cite
|
Sign up to set email alerts
|

Marine biofilms constitute a bank of hidden microbial diversity and functional potential

Abstract: Recent big data analyses have illuminated marine microbial diversity from a global perspective, focusing on planktonic microorganisms. Here, we analyze 2.5 terabases of newly sequenced datasets and the Tara Oceans metagenomes to study the diversity of biofilm-forming marine microorganisms. We identify more than 7,300 biofilm-forming ‘species’ that are undetected in seawater analyses, increasing the known microbial diversity in the oceans by more than 20%, and provide evidence for differentiation across oceanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 67 publications
(75 reference statements)
9
111
0
Order By: Relevance
“…Surface adhesion presents organisms with advantages, for example, greater nutritional access, physical protection, and environmental stability. Biofilm inhabitants also excrete chemical cues that affect invertebrate recruitment and forms of metabolic cooperation (e.g., quorum sensing; Socransky & Haffajee, ; Zhang et al, ). Further supporting the important ecological role of biofilms, Zhang et al () recently identified 7,300 new species from metagenomics data from biofilm‐forming microorganisms.…”
Section: Fate Of Microplastics In the Oceanmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface adhesion presents organisms with advantages, for example, greater nutritional access, physical protection, and environmental stability. Biofilm inhabitants also excrete chemical cues that affect invertebrate recruitment and forms of metabolic cooperation (e.g., quorum sensing; Socransky & Haffajee, ; Zhang et al, ). Further supporting the important ecological role of biofilms, Zhang et al () recently identified 7,300 new species from metagenomics data from biofilm‐forming microorganisms.…”
Section: Fate Of Microplastics In the Oceanmentioning
confidence: 99%
“…Most previous work to identify marine species focused on free‐living forms. The additions of Zhang et al () increased the known microbial diversity of the oceans by more than 20%. Clearly, factors that influence or alter the formation and evolution of biofilm communities may have profound impacts on ecological communities in aquatic systems, in general.…”
Section: Fate Of Microplastics In the Oceanmentioning
confidence: 99%
“…Future studies on marine biofilms addressing the exploration of their biodiversity [129] and their ecological role in ecosystem functioning should be encouraged, also considering the role of microbes as catalysts of biogeochemical nutrient cycling [130,131]. Marine biofilms could also be used as indicators of water quality, in relation to the well-known ability of microbes as sentinels of environmental changes in several temperate and polar marine environments [132][133][134] as well as in tropical coral reef ecosystems [135].…”
Section: Future Research Directionsmentioning
confidence: 99%
“…We showed that ALAN can affect even these naturally highly stressed communities, either directly or indirectly by affecting positive species interactions. This might impair a variety of key ecosystem functions, including fluxes of chemical elements and degradation and recycling of organic matter (Dang & Lovell, ; Falkowski, Barber, & Smetacek, ; Hölker et al, and literature therein), as well as still unknown functional potentials of microbial biofilms (Zhang et al, ). We believe that night light pollution must be considered as an additional key driver of change in these systems, able to interact with or add to global and local stressors currently impinging on coastal areas.…”
Section: Discussionmentioning
confidence: 99%